Developing multi-stakeholder forest management scenarios: a multi-agent system simulation approach applied in Indonesia - Purnomo, H.; Mendoza, G.A.; Prabhu, Ravi; Yasmi, Yurdi (2005)
Participatory approaches to development in general and natural resource management in particular are now a widely accepted management strategy. Multi-agent system (MAS), a computer-based tool, offers a promising approach for multi-stakeholder management systems such as the case involving community-managed resources. MAS provides a framework where stakeholders’ (or agents) individual actions, behaviors and rational decisions can be analyzed in the context of the other stakeholders’ actions and decisions. This robust approach offers a convenient analytical framework that can be used to simulate agents’ actions, reactions and interactions. The approach also provides an environment where strategies or multi-stakeholder forest management scenarios can be developed and analyzed. This paper describes a MAS model developed for a forest management unit located in East Kalimantan, Indonesia. Results and experience gained from the case study suggest that MAS is a suitable approach for developing multi-stakeholder forest management strategies.